Case report: Misdiagnosed orolingual dyskinesia as a consequence of seizures in a chorea-acanthocytosis patient with a novel VPS13A variation from a family with consanguineous marriage - Wang, Mengying; Li, Huimin; Zhou, Qing; Zhao, Qin; Wang, Man; Geng, Yumei; Kang, Huicong (Frontiers in Neurology, 2024)
Chorea-acanthocytosis (ChAc) is a rare autosomal recessive inherited syndrome with heterogeneous symptoms, which makes it a challenge for early diagnosis. The mutation of VPS13A is considered intimately related to the pathogenesis of ChAc. To date, diverse mutation patterns of VPS13A, consisting of missense, nonsense, and frameshift mutations, have been reported. In this study, we first report a clinical case that was misdiagnosed as epilepsy due to recurrent seizures accompanied by tongue bite for 9 months, which was not rectified until seizures were controlled and involuntary orolingual movements with awareness became prominent and were confirmed to be orolingual dyskinesia. The patient was eventually diagnosed as ChAc based on whole-exome sequencing revealing novel homozygous c.2061dup (frameshift mutation) and c.6796A > T dual mutations in VPS13A. The patient from a family with consanguineous marriage manifested epileptic seizures at onset, including both generalized tonic–clonic seizures and absence but normal long-term electroencephalography, and gradually developed orofacial dyskinesia, including involuntary tongue protrusion, tongue biting and ulcers, involuntary open jaws, occasionally frequent eye blinks, and head swings. The first test of the peripheral blood smear was negative, and repeated checks confirmed an elevated percentage of acanthocytes by 15–21.3%. Structural brain MRI indicated a mildly swollen left hippocampus and parahippocampal gyrus and a progressively decreased volume of the bilateral hippocampus 1 year later, along with atrophy of the head of the caudate nucleus but no progression in 1 year. We deeply analyzed the reasons for long-term misdiagnosis in an effort to achieve a more comprehensive understanding of ChAc, thus facilitating early diagnosis and treatment in future clinical practice.